Konieczność - wytrwałość - produktywność, czyli LEONI Productivity System - Ćwiklak, Adam (Necessity - Perseverance - Productivity : LEONI Productivity System, 2006)
A company willing to be successful faces a necessity to take a breakthrough decision of innovating its systems of management. The company should not remain passive and implement new systems only when it is forced to. It should rather plan innovations consciously and implement new solutions consistently. Perseverance and consistency as well as patience are the prerequisites of a successful implementation of such decisions. The immediate result of such a philosophy is not only higher productivity of the organization but also progress in its development. The company is becoming a learning and more flexible organization. Such conclusions can be drawn on the analysis of LEONI Productivity System.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 473-481